Odpowiedź :
Odpowiedź:
13. D
14. B
16. B
17. C
18. B
20.
a) 3a - 2b + 5
b) 3x - 2y + 1
c) -x + 9
Odpowiedź:
Zad. 13
D
Zad.14
B
Zad.15
A. 6a + 2 = 6 * (-2) + 2 = - 12 + 2 = -10
B. - x + 5y + 9 = -4 + 5 * (-0,3) + 9 = - 4 - 1,5 + 9 = 3,5
Zad.16
3x - 4 - 3 - x = 2x - 7
Odp.B
Zad.17
Odp. C
Zad. 18
Odp. B
Zad. 19
Przekształcenie 2 jest poprawne
Zad. 20
A. 3a - 2b + 5
B. 3x - 2y + 1
C. 5x + 7 - 6x + 2 = - x + 9
Zad.21
[tex]a.2 {}^{2} - 6x + 10 - 2x {}^{2} + x - 3 = - 5x + 7 = - 5 \times ( - 1.2) + 7 = 13[/tex]